A Comprehensive Review of the Quadratic High Gain DC-DC Converter for Fuel Cell Application - Divya Navamani Jayachandran; Jagabar Sathik; Tanmay Padhi; Aditi Kumari (International Journal of Electronics and Telecommunications, 2022)
In the recent times, lot of research work carried out in the field of fuel cells explicitly divulges that it has the potential to be an ultimate power source in upcoming years. The fuel cell has more storing capacity, which enables to use in heavy power applications. In these applications, power conditioning is more vital to regulate the output voltage. Hence, we need a dc-dc converter to provide a constant regulated output voltage for such high-power system. Currently, many new converters were designed and implemented as per the requirement. This paper has made comparative study on several topologies of the quadratic high gain dc-dc converter and the applications where these topologies can be used when the fuel cell is given as a source. Also, we have compared various parameters of all the converters considered and generated the results with steady-state and dynamic study. In this article, we briefed the types of analysis carried on the dc-dc converter to study its performance. Moreover, various application of fuel cell is presented and discussed. This paper will be a handbook to the researchers who start to work on high gain dc-dc converter topologies with quadratic boost converter as a base. This article will also guide the engineers to concentrate on the fuel cell components where it needs to be explored for optimizing its operation.